An instructional media center for MSU-Iligan Institute of Technology a proposal - Alensub, Sonia M. 1948-
This study is a proposal to organize the Instructional Media Center (IMC) for MSU-Iligan Institute of Technology. The standard procedure began with the initial survey of the human and material resources obtained in the institute and an examination of the academic programs and problems of the institute. Based on the findings and on the standards for the administration and staffing, structure, functions, location, size, instructional media requirements, services and financing of an IMC, the IMC appropriate to meet the needs of that particular institution is designed and proposed. The researcher hoped that through the results of the study, the quality and quantity of the manpower produced by IIT would consequently improve and would meet the demands of the commercial and industrial segments of Iligan City and Mindanao.